Doses and split nitrogen fertilizer applications on the productivity and quality of arugula1 - Nascimento, Camila Seno [UNESP]; Nascimento, Carolina Seno [UNESP]; Filho, Arthur Bernardes Cecílio [UNESP] (FapUNIFESP (SciELO), 2021)
Splitting nitrogen (N) fertilizer application can be an efficient nutrient management technique to improve productivity and plant quality, as well as to reduce the negative environmental impact caused by N losses. In this context, the present study investigated how the management of N affects the agronomic characteristics of field-grown arugula plants. Nine treatments were assessed in a randomized complete block design, in a 4 x 2 + 1 factorial scheme, with three replicates. The evaluated factors were doses of N (60, 120, 180 and 240 kg N ha-1), split N fertilizer applications at side-dress (two and three times) and an additional treatment without a N supply. Maximum height was obtained with the application of 198 kg N ha-1. Nitrate content, fresh mass and productivity increased with increasing N doses. There was no effect of split N fertilizer applications on the characteristics evaluated. Therefore, the supply of 240 kg N ha-1 divided into two portions was considered as the best management strategy.
Doses e parcelamento da adubação nitrogenada na produtividade e qualidade da rúcula
Keywords: Eruca sativa; Mineral nutrition; Nitrate